Outcome of deceased donor renal transplantation in patients with an ileal conduit. (30th January 2014) - McLoughlin, Louise C.; Davis, Niall F.; Dowling, Catherine M.; Power, Richard E.; Mohan, Ponusamy; Hickey, David P.; Smyth, Gordon P.; Eng, Molly M.P.; Little, Dilly M.
Abstract Renal transplantation in recipients with an ileal conduit is uncommon and occasionally controversial as it has been associated with high morbidity and mortality rates. We report on 17 patients with an ileal conduit who received a deceased donor renal transplant at our institution between January 1986 and December 2012. We retrospectively reviewed their allograft and surgical outcome. There were four mortalities at five, five, 39, and 66 months post‐transplant. Sixteen of 17 grafts functioned immediately; one patient had primary non‐function secondary to vascular thrombosis. Thirteen of 17 (76.5%) grafts were functioning at a mean follow‐up period of 105 months. The mean serum creatinine at follow‐up was 111 μM (±38.62). Five patients had seven episodes of urosepsis requiring hospital admission, and five patients received treatment for renal stone disease. We conclude that given improvements in immunosuppression, surgical technique, infection treatment, and selection criteria, we believe that renal transplantation in the patient with an ileal conduit yields excellent graft survival, although there is a high morbidity rate in this cohort of patients in the long term.